The Comparison of Total Cholesterol Level in DMPA and Combination Injection Contraception Users - Rara Yumna Elfrida; Gadis Meinar Sari; Sri Ratna Dwiningsih; Pudji Lestari (Universitas Airlangga, 2020)
Introduction: Hormonal injection contraception is the most widely used method of contraception in Indonesia. In long-term use, one of the side effects of injection contraception is changes in lipid metabolism in the body caused by the accumulation of hormones in the body. Two types of injectional contraception are widely used in Indonesia, namely combined injection and DMPA injection; different hormonal content has various side effects on the lipid profile. This study aimed to compare the total cholesterol level between acceptors of DMPA injection and combined injection.Methods: This study used an observational analytic method with a cross-sectional approach. The sample size is 60 respondents, including 30 DMPA injection acceptors and 30 combination injection acceptors. The sampling method uses a purposive sampling technique The independent variable in this study was the total cholesterol level of the acceptor, and the dependent variable was the acceptor of DMPA injection and the combination injection acceptor. Analysis of research data used the Independent T-test with α=0.05.Results: The results of the bivariate analysis found significant differences in total cholesterol levels in the DMPA injection contraception acceptor and combination injection with p= 0.037. It was found that overall cholesterol levels of DMPA injection acceptors were higher.Conclusion: There is a difference in total cholesterol levels in the DMPA injection contraception acceptor with a combination injection contraception acceptor.